2002
DOI: 10.2166/wqrj.2002.026
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Oxygen Demand and Acute Toxicity during Batch Biological Treatment of a Petroleum Refinery Effluent

Abstract: This study was undertaken in order to investigate the removal of oxygen demand and acute toxicity from a petroleum refinery effluent. The results of this study provide a better understanding of the biodegradation process occurring at the Chevron refinery wastewater treatment plant (WWTP) in Burnaby, BC. The WWTP consists of a deep shaft bioreactor followed by a dissolved air flotation clarifier and effluent polishing biofilters. The treatment plant is able to degrade approximately 75% of the COD and 95% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…NAs are corrosive and acutely toxic to both aquatic and terrestrial species, including bacteria, yeast, earthworms, fish, mammals, and both aquatic and terrestrial plants (Armstrong et al, 2008;Clemente et al, 2003;Frank et al, 2009Frank et al, , 2008Holowenko et al, 2002;Nero et al, 2006;Peters et al, 2007;Rogers et al, 2002;Sarathy et al, 2002;Scott et al, 2008;Thomas et al, 2009). NAs can be degraded under aerobic conditions; however, many NAs are persistent and remain in the wastewater systems even after biotreatment (Clemente and Fedorak, 2005;Del Rio et al, 2006;Quagraine et al, 2005a;Scott et al, 2005;Misiti, 2012;Misiti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…NAs are corrosive and acutely toxic to both aquatic and terrestrial species, including bacteria, yeast, earthworms, fish, mammals, and both aquatic and terrestrial plants (Armstrong et al, 2008;Clemente et al, 2003;Frank et al, 2009Frank et al, , 2008Holowenko et al, 2002;Nero et al, 2006;Peters et al, 2007;Rogers et al, 2002;Sarathy et al, 2002;Scott et al, 2008;Thomas et al, 2009). NAs can be degraded under aerobic conditions; however, many NAs are persistent and remain in the wastewater systems even after biotreatment (Clemente and Fedorak, 2005;Del Rio et al, 2006;Quagraine et al, 2005a;Scott et al, 2005;Misiti, 2012;Misiti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, use of advanced mass spectrometry techniques has shown that oil sands process-affected water (OSPW) and oil field and refinery wastewaters contain low levels of NAs with a broad spectrum of molecular structures. The range of NA structures has recently been expanded to include other polar and N- and S-containing heteroatomic species and aromatic species found in the oil sands acid extractable fraction. , NAs in the wastewater is an ecological concern, as NAs are among the most toxic components of both OSPW and refinery process wastewater. The degree of toxicity depends on the concentration of NAs as well as their type and molecular structure. , …”
Section: Introductionmentioning
confidence: 99%
“…NAs are corrosive and among the most toxic components of oil sands process waters, acutely toxic to both aquatic and terrestrial species, including bacteria, yeast, earthworms, fish, mammals, and both aquatic and terrestrial plants (Armstrong et al, 2008;Clemente et al, 2003;Frank et al, 2009Frank et al, , 2008Holowenko et al, 2002;Nero et al, 2006;Peters et al, 2007;Rogers et al, 2002;Sarathy et al, 2002;Scott et al, 2008;Thomas et al, 2009). Model NAs, commercial NA mixtures and NAs in oil sands process water samples have been found to degrade aerobically using inocula obtained from oil sands process waters and NA-affected natural systems; however, commercial NAs were found to be more readily degraded than the NAs in oil sands process waters (Clemente and Fedorak, 2005;Del Rio et al, 2006;Scott et al, 2005).…”
Section: Introductionmentioning
confidence: 99%